2018
DOI: 10.1099/mic.0.000605
|View full text |Cite|
|
Sign up to set email alerts
|

Streptomyces coelicolor strains lacking polyprenol phosphate mannose synthase and protein O-mannosyl transferase are hyper-susceptible to multiple antibiotics

Abstract: Polyprenol phosphate mannose (PPM) is a lipid-linked sugar donor used by extra-cytoplasmic glycosyl tranferases in bacteria. PPM is synthesiszed by polyprenol phosphate mannose synthase, Ppm1, and in most Actinobacteria is used as the sugar donor for protein O-mannosyl transferase, Pmt, in protein glycosylation. Ppm1 and Pmt have homologues in yeasts and humans, where they are required for protein O-mannosylation. Actinobacteria also use PPM for lipoglycan biosynthesis. Here we show that ppm1 mutants of Strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…Mannosylation of the high-affinity phosphate-binding protein PstS by Pmt has been reported in Streptomyces (54), and insertions in SCO4142 ( pstS ) increased ACT production, suggesting that the decreased ACT production seen in the mannosylation mutants may be, at least in part, due to altered regulation of phosphate uptake. In addition, as a pmt mutant lost intrinsic functions of the cell envelope (55), the decreased ACT production of our pmt mutant may be caused by cell envelope damage.…”
Section: Discussionmentioning
confidence: 97%
“…Mannosylation of the high-affinity phosphate-binding protein PstS by Pmt has been reported in Streptomyces (54), and insertions in SCO4142 ( pstS ) increased ACT production, suggesting that the decreased ACT production seen in the mannosylation mutants may be, at least in part, due to altered regulation of phosphate uptake. In addition, as a pmt mutant lost intrinsic functions of the cell envelope (55), the decreased ACT production of our pmt mutant may be caused by cell envelope damage.…”
Section: Discussionmentioning
confidence: 97%
“…The synthesis of polyprenol phosphate mannose by Ppm1 is therefore an important activity and ppm1 mutants are considerably less fit than the parent strains [ 11, 12 ]. In the case of S. coelicolor, ppm1 - mutants have a small colony growth phenotype and are hyper-susceptible to multiple antibiotics, most of which inhibit cell wall biogenesis suggesting that these mutants are pleiotropically deficient in membrane and/or periplasmic function (Howlett et al , [ 4 ]). Mutants lacking Ppm1 or Pmt are also resistant to phage infection and we have proposed that φC31 uses a glycoprotein(s) as its receptor [ 6, 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that strains of S. coelicolor lacking the ability to synthesise polyprenol phosphate mannose due to mutations in polyprenol phosphate mannose synthase (Ppm1) were hyper-sensitive to multiple antibiotics (Howlett et al ., [ 4 ]). We used RNA-seq and Raman spectroscopy to demonstrate that the strains had undergone changes to the membrane phospholipids, with possible subsequent changes to membrane functions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations